Studies in Family Planning 2022
DOI: 10.5772/intechopen.104941
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Its Consequences on Male and Female Reproductive Health

Abstract: Smoking contributes to the death of around one in 10 adults worldwide. Specifically, cigarettes are known to contain around 4000 toxins and chemicals that are hazardous in nature. The negative effects of smoking on human health and interest in smoking-related diseases have a long history. Among these concerns are the harmful effects of smoking on reproductive health. Thirteen percent of female infertility is due to smoking. Female smoking can lead to gamete mutagenesis, early loss of reproductive function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…Houda et al in 2022 showed that after being too exposed to smoking, they have fertility problems including poor semen parameters (Houda et al, 2022). Overall, altered methylation in spermatogenesis‐related genes impairs reproductive function, supporting the hypothesis that sperm DNA methylation affects infertility (Rotondo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Houda et al in 2022 showed that after being too exposed to smoking, they have fertility problems including poor semen parameters (Houda et al, 2022). Overall, altered methylation in spermatogenesis‐related genes impairs reproductive function, supporting the hypothesis that sperm DNA methylation affects infertility (Rotondo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%